The Transformational Role of Entrepreneurial Universities in Fostering Tourism Sector of Kazakhstan: Legal Documentary Analysis - BAYANBAYEVA, Aigerim; MAKHMADINOV, Dauletkeldi; MYRZATAYEV, Nurmukhamed; NIYETALINA, Gaukhar; NARBAYEVA, Gulmira; SULEIMENOVA, Saule; ALTYNBASSOV, Bakhyt (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023, 2023)
This article examines the role of entrepreneurial universities in shaping Kazakhstan's tourism industry by fostering tourism innovation. It focuses on the ways in which these universities contribute to the development of the tourism sector in Kazakhstan, including curriculum enhancement, research projects, industry partnerships, and the promotion of entrepreneurial culture. By using documentary analysis as a research method, this study seeks to examine existing literature, reports, policy documents, and other relevant sources to gather insights on the contributions of entrepreneurial universities in the tourism sector. This article sheds light on the unique challenges and opportunities that Kazakhstan faces in the development of its tourism sector. It stresses the role of entrepreneurial universities in addressing these challenges to promote Kazakhstan as a compelling tourism destination. The findings of this study highlight the significance of entrepreneurial universities in promoting innovation, knowledge transfer, and entrepreneurship education within the tourism sector and provide valuable information for policymakers, the academic community and industry professionals in understanding the crucial role of entrepreneurial universities in advancing the tourism sector in Kazakhstan. It concludes that by promoting partnerships between universities, government, and industry stakeholders, Kazakhstan can create an ecosystem that encourages tourism innovation and sustainable development of the tourism sector. By leveraging the resources, knowledge, and networks of entrepreneurial universities, Kazakhstan can develop a dynamic tourism sector that draws tourists from across the world and promotes economic growth.